Penerapan Terapi Active Cycle of Brething Tehnique untuk Mengatasi Bersihan Jalan Nafas Tidak Efektif pada Pasien TB Paru - Roslinde Sitanggang; Aniska Indah Fari; Bangun Dwi Hardika (Jurnal Rumpun Ilmu Kesehatan, 2026)
Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacteria tuberculosis (M.TB). Pulmonary TB cases continue to increase every year. Patients with Pulmonary TB often experience in the respiratory tract, this disorder can inhibit daily activities and even have the potential to be life-threatening if not treated appropriately. One of the ways used to overcome this disorder is the Active Cycle of Breathing Technique, which can help control breathing patterns to become more regular. Analysis of Nursing Care in Pulmonary TB Patients with the Application of Active Cycle of Breathing Technique Therapy to Overcome Ineffective Airway Clearance in Pulmonary Tuberculosis Patients.The design used is analytical descriptive research. This research technique was by measuring breathing and oxygen saturation before the application of ACBT, then respondents were given an active cycle breathing technique intervention and evaluated after 5 minutes. Each respondent was given ACBT intervention 1 time a day for 3 consecutive days for 15 minutes.This case study showed an increase in airway clearance disorders after the application of active cycle of breathing therapy in the three respondents with a decrease in respiratory frequency. Active cycle therapy of brething technique improves airway clearance is ineffective in patients with Pulmonary TB. Suggestion: Active cycle of brething respiratory therapy can be one of the non-pharmacological therapies to reduce airway clearance disorders in pulmonary TB patients.